2004
DOI: 10.1002/msc.54
|View full text |Cite
|
Sign up to set email alerts
|

A review of the history of hand exercises in rheumatoid arthritis

Abstract: The management of the hand in the patient with rheumatoid arthritis (RA) is a challenge to all therapists and evidence for optimum management historically scarce. Given that it is estimated that hands and wrists are affected in 80-90% of RA patients (Maini and Feldmann, 1998), it is apparent that this is an important area for both the patient and practitioner. While acknowledging the importance of hand function to the patient with RA (Jones et al., 1991), it should also be admitted that there is little researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…[20] Although there is no clear evidence for the control of hand deformity and joint destruction by physical agents and exercise, these modalities are used to relieve hand pain, stiffness, and weakness. [5,10,21] Cima et al [22] randomly assigned women with RA and hand deformity to two groups (n=13), and the study group performed exercises to strengthen the intrinsic and extrinsic muscles of the hands, and no exercise was performed by the control group (n=7). The patients in the study group performed exercises once daily and five days in a week under the supervision of a physiotherapist and performed 20 sessions of home exercises for two months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20] Although there is no clear evidence for the control of hand deformity and joint destruction by physical agents and exercise, these modalities are used to relieve hand pain, stiffness, and weakness. [5,10,21] Cima et al [22] randomly assigned women with RA and hand deformity to two groups (n=13), and the study group performed exercises to strengthen the intrinsic and extrinsic muscles of the hands, and no exercise was performed by the control group (n=7). The patients in the study group performed exercises once daily and five days in a week under the supervision of a physiotherapist and performed 20 sessions of home exercises for two months.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is no consensus regarding frequency of exercises, such as twice daily, daily, or twice weekly. [21] The researchers of this study preferred CEP due to the fact that the patients easily learned how to perform this exercise and they continued to perform the exercises at home twice daily without need for further supervision. The exercises were gentle and therefore well-tolerated by the patients, and did not cause an increase in inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Using our hands in daily activities is the natural way to maintain or improve hand function. For many years, patients with rheumatic diseases were recommended to avoid heavy activities and intensive exercising (50).…”
Section: Recommendations For Hand Exercises In Hand Oamentioning
confidence: 99%
“…However, comparatively little research has evaluated the evidence for the benefits of hand exercise in RA (O'Brien, Jones et al 2006). Recently reviewed effectiveness on hand exercise therapy in RA patients showed that only nine eligible studies have incorporated hand exercise therapy as part of the intervention (Chadwick 2004;Wessel 2004). Hoening et al (1993) showed in their study that a home hand exercise program was effective for increasing the grip force in the RA hand (Hoenig, Groff et al 1993).…”
Section: Rehabilitation and Intervention Of The Rheumatoid Arthritis mentioning
confidence: 99%